PENGARUH PENERAPAN GOOD GOVERNANCE DAN SISTEM AKUNTANSI KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH KOTA MANADO - Maramis, Miranda Miryam; Morasa, Jenny; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2018)
This study aims to analyze the application of good governance and local financial accounting system to the quality of financial statements SKPD. This research was conducted in Manado City Government. Sampling method in this research is by using quantitative approach, by using primary data through questionnaire. This sample is distributed to 40 financial officers from 10 SKPD of Manado City. For this study data were analyzed by using multiple linear regression with statistical program tool, after classical assumption test fulfilled. The data is processed by using SPSS 21 program. The result of this research indicates that good governance has a significant positive influence to the quality of local financial statements and regional financial accounting system there is no significant positive effect on the quality of local financial statements.Keywords: Good Governance, Regional Financial Accounting System, Quality of Regional Financial Report